Utilization of mine tailings from copper-gold mining process as fine aggregates of roller compacted concrete - Gopez, Renato G. (Animo Repository, 2002)
This paper presents the study on the use of mine tailings as an alternative or substitute construction material. It is focused on the feasibility of using mine tailings as fine aggregates instead of sand in a roller compacted concrete (RCC). The mine tailings used were obtained from Tailings Dam #2 of Philex Minig Corp. in Padcal, Tuba, Benguet. These tailings consist of finely ground siliceous particles processed by series of crushing, sizing, grinding, and concentrating ore to extract copper and gold. A comprehensive experimental program was conducted to investigate the strength, and durability of roller compacted concrete with Philex mine tailings as fine aggregates. It was then compared with lahar aggregate concrete and RCC with Porac sand. Various mixtures of RCC with low, medium, and high cement contents were mixed and cast. The strength at 28 days of RCC containing mine tailings and sand ranged from 17 to 28 MPa and 17 to 37 MPa, respectively, at dry density of 2350 to 2450 kg/cum. The durability of RCC with mine tailings was evaluated by subjecting the specimens to an alternate wetting and drying cycles. The remaining strength of 18.7 MPa after 15 cycles indicates that it could endure stresses due weather changes in the Philippines. Based on the results of various tests conducted, it shows that Philex mine tailings has the potential to be a substitute of sand or an alternative fine aggregates in a roller compacted concrete. Specific recommendations were formulated on the work done for further development and eventual introduction in the construction industry.